Analysis of the Implementation of the Kurikulum Merdeka at SD Negeri 3 Karangsalam Based on the Scriven Evaluation Model - Yanuar Prima Nur Hakim; Sriyanto Sriyanto (UM Purwokerto Press, 2025)
This study aims to evaluate the effectiveness of the implementation of the Kurikulum Merdeka at SD Negeri 3 Karangsalam using the Scriven Evaluation Model. The analysis was conducted through both formative and summative evaluations. The formative evaluation encompassed four key aspects: the clarity of curriculum objectives, the relevance of instructional materials, the implementation of instructional methods, and assessment practices. Meanwhile, the summative evaluation assessed program effectiveness, implementation efficiency, stakeholder satisfaction, and the overall impact of the curriculum. This research employed a descriptive-evaluative method using both qualitative and quantitative approaches. Evaluation instruments were developed based on indicators from the Scriven Model. Data were collected through official school document analysis, classroom observations, interviews, surveys administered to teachers, students, and parents, as well as student learning outcomes. The data were then analyzed and compared with the evaluation instruments. The results indicate that the implementation of the Kurikulum Merdeka is categorized as effective, with a formative evaluation score of 79.35% and a summative evaluation score of 79.94%. These findings suggest that the curriculum has been implemented optimally and has positively influenced both the learning process and student outcomes. The study recommends ongoing evaluations to support continuous improvement in curriculum implementation quality.